Electrochemical Synthesis Of Tin Sulphide In Aqueous Media - Ghazali, Arniza (2000)
Chalcogenide semiconductor of the type tin sulphide or stannous sulphide (SnS) has been synthesised in aqueous media under the presence and absence of EDT A complexing agent. It was found that electrodeposition performed in the presence of EDTA is more reproducible, better adhered to titanium substrate, more leveled, more crystalline and offers better photoconductivity properties in comparison to electrodeposition carried out without EDT A. These were determined by means of Energy Dispersive Analysis of X-ray (EDAX), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), IN-visible Spectroscopy, Linear Scan Photovoltammetry (LSPV) and in special cases, X-ray Photoelectron Spectroscopy (XPS).